Juridic Review of the Implementation of the Principle of Good Faith in Online Buying Transactions - Cristien Latidi (Universitas Negeri Gorontalo, 2021)
This study discusses the juridical review of the application of the principle of good faith in online buying and selling transactions. The objectives of this research are; To find out how the juridical review of the application of the principle of good faith To find out what are the inhibiting factors for the application of the principle of good faith in online buying and selling transactions. The method used in this research is empirical normative research, which means to analyze research based on library data and based on the state of variables, and the phenomena that occur when the research takes place and presents it as it is. The results of the study show that to realize the principle of good faith in online buying and selling transactions, the government has regulated it in Article 1338 of the Civil Code which reads